PENGARUH KINERJA KEUANGAN DAN MEKANISME GOOD CORPORATE GOVERNANCE TERHADAP ISLAMIC SOCIAL REPORTING (ISR) (Pada Bank Umum Syariah di Indonesia Periode 2014-2018) - Rachmania, Dewi; Alviana, Nurul (Universitas Muhammadiyah Tangerang, 2020)
This study aims to study the Effect of Financial Performance and Good Corporate Governance (GCG) Approaches to Islamic Social Reporting (ISR) in Islamic Commercial Banks (BUS). The methodology used in this study uses purposive sampling, the samples obtained were 9 companies so that there were 45 observational data. The data analysis method used is panel data regression analysis processed using E-views 9.0. The results of this study indicate that the profitability proxied by Return on Assets (ROA) does not have a significant effect on Islamic Social Reporting (ISR) with a Prob value of 0.6739, leverage proxied by Debt to Equity Ratio (DER) has a significant positive effect on Islamic Social Reporting (ISR) with a value of Prob 0.0341, the board of commissioners does not have a significant influence on Islamic Social Reporting (ISR) with a value of 0.2572 Prob, and the audit committee has a significant positive effect on Islamic Social Reporting (ISR) with a Prob value of 0.0089.